Relationship of anti-GM-CSF antibody concentration, surfactant protein A and B levels, and serum LDH to pulmonary parameters and response to GM-CSF therapy in patients with idiopathic alveolar proteinosis - Seymour, J (BMJ Group, 2003)
Methods: Blood levels of anti-GM-CSF antibodies, SP-A, SP-B, LDH, and [A – a]DO(2), VC, and TLCO were measured before rhGM-CSF treatment and every 2 weeks thereafter in 14 patients with AP. Results: At baseline, high levels of anti-GM-CSF antibodies and increased SP-A and SP-B levels were seen in all patients, and LDH was raised in 83%. SP-A was highly correlated with [A – a]DO(2), VC, and TLCO (p≤0.02), but other markers were not. Only a normal LDH level was predictive of a response to rhGM-CSF treatment (p=0.03). During treatment a correlation between conventional and serological variables within patients was seen only between SP-A and [A – a]DO(2) (p=0.054), LDH levels and [A – a]DO(2) (p=0.010), and LDH levels and VC (p=0.019). Conclusions: Of the serological parameters studied, only SP-A and LDH levels were correlated with conventional measures of disease severity, with LDH most accurately reflecting [A – a]DO(2) and vital capacity. Only a normal LDH level predicted a higher likelihood of response to treatment with GM-CSF.